A Wireworm Glyphonix bimarginatus (Schaeffer) (Insecta: Coleoptera: Elateridae) - Dakshina R. Seal; Rafia A. Khan (EDIS, 2019)
Glyphonix bimarginatus (Figure 1) is a common click beetle pest of various economically important crops. The larvae of click beetles (Coleoptera: Elateridae) are elongated, wire-like and commonly known as wireworms. Wireworms are considered as subterranean economic pests during their larval stages in many parts of the world including the United States. The larvae of Glyphonix bimarginatus are commonly found with larvae of other click beetles in the field. Larvae of Glyphonix bimarginatus occurs in soil rich in organic matter and rarely in sandy soil. Young roots and germinating seeds are commonly fed upon by the larvae.